Pengaruh Sentiment Analysis Berdasarkan Electronic Word of Mouth yang Dihasilkan dari Social Media Marketing Activities terhadap Posisi Bersaing Janji Jiwa dan Kopi Kenangan - Saffania Zahra Aina Halinda; Hasrini Sari (Journal of Research in Industrial Engineering and Management, 2025)
Today's fierce business competition can affect the competitive position of a brand, and with the development of technology in the digital era changing consumer behavior that has a dependence on the internet network in communicating opinions, information, and transactions that influence each other or what is commonly called Electronic Word of Mouth (E-WOM). In E-WOM itself, there are sentiments that can be analyzed to determine whether the meaning of the sentence is positive, negative, or neutral. The sentiment is what the brand needs to know the perspective of the market. The development of this digital era also requires a brand to have a social media account to make an assessment first before deciding on a purchase. Brands that have a positive and strong image in the minds of consumers or followers are believed to be able to attract consumer interest in buying products offered by a brand. This research was conducted by looking at the quality of Sentiment Analysis from each coffee shop brand on Electronic Word of Mouth (E-WOM) generated by Social Media Marketing Activities on Instagram social media. The case study was conducted on business competition between two coffee shop brands Janji Jiwa and Kopi Kenangan, because based on the brand index of the Top Brand Award the two coffee shops are in a very tight competitive position. Sentiment analysis was conducted using Python and Jupyter. The results showed that Janji Jiwa coffee shop has a positive comment weight of 14.90%, which is higher than Kopi Kenangan coffee shop that has a positive comment weight of only 11.70% with the weight of negative comments owned by both coffee shop brands amounting to 73.30%. Positive sentiment. The positive comment weights reflect the competitive positioning of the two brands, with Janji Jiwa being in a stronger position than Kopi Kenangan.